2023
DOI: 10.37934/araset.29.2.204211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenolic Compound, Colour Value, and Antioxidant Activity of Roselle Calyces Extract Between Modified Supercritical Carbon Dioxide and Conventional Extraction

Abstract: Supercritical carbon dioxide (SC-CO2) is a clean and green technology for extracting polyphenols and antioxidants from roselle (Hibiscus Sabdariffa) as nutraceutical ingredients and high-value co-products development. To increase the SC-CO2 fluid affinity towards polar compounds, general regard as a safe (GRAS) solvent, ethanol-water was added in a small amount as a modifier. Dry roselle calyces were extracted using modified SC-CO2 and conventional methods (Soxhlet and Shaking Water Bath) to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Research results Lestyo et al, [8], Rani Sauriasari et al, [10] showed that the character of phenol compounds in matoa leaves is a compound belonging to the flavonoid group. Phenolic compounds are active compounds of secondary metabolites which are known to have several properties, namely as astringents, antidiarrheals, antibacterials , and antioxidants [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Research results Lestyo et al, [8], Rani Sauriasari et al, [10] showed that the character of phenol compounds in matoa leaves is a compound belonging to the flavonoid group. Phenolic compounds are active compounds of secondary metabolites which are known to have several properties, namely as astringents, antidiarrheals, antibacterials , and antioxidants [10,11].…”
Section: Introductionmentioning
confidence: 99%